Reappearance of Aedes aegypti (Diptera: Culicidae) in Lima, Peru - Carlos Sevilla Andrade; Abraham G Cáceres; Aldo Vaquerizo; Sergio Ibañez-Bernal; Lourdes Sulca Cachay (Memorias do Instituto Oswaldo Cruz, 2001)
We report here the reappearence of Aedes aegypti in the Rimac district, and summarize the history of this mosquito species in Peru since its first detection in 1852. On March 17 2000 were found Ae. aegypti and Culex quinquefasciatus in Mariscal Castilla town, Flor de Amancaes, San Juan de Amancaes, El Altillo and Santa Rosa in the Rimac district, Lima Province.